2019
DOI: 10.15642/ijet2.2019.8.1.9-22
|View full text |Cite
|
Sign up to set email alerts
|

British or American? Iranian EFL learners’ Perceptions toward English Accents: Exploring possible relationships

Abstract: Native English accents (British and American) are known as highly favored and accepted varieties compared to other existing accents in English as foreign language (EFL) context. Notwithstanding the research accomplished on EFL learners’ attitudes toward either of the accents (British or American), studies are still scant regarding the investigation of their perspectives in detail toward one of the accents specifically within the context of Iran. The aim of this study is to examine the Iranian EFL learners’ att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
(32 reference statements)
0
6
1
Order By: Relevance
“…However, the students associated GA with greater solidarity and stronger affiliative feelings. Contrary to these two studies, Weisi et al (2019) found university students' disposition toward American English among Iranian students. Of the plethora of research accomplished on this topic, only one study (Rashid, 2011) has been conducted regarding Iraqi university students' attitudes toward and preferences for American and British English.…”
Section: Attitudes Toward English Accentscontrasting
confidence: 83%
See 4 more Smart Citations
“…However, the students associated GA with greater solidarity and stronger affiliative feelings. Contrary to these two studies, Weisi et al (2019) found university students' disposition toward American English among Iranian students. Of the plethora of research accomplished on this topic, only one study (Rashid, 2011) has been conducted regarding Iraqi university students' attitudes toward and preferences for American and British English.…”
Section: Attitudes Toward English Accentscontrasting
confidence: 83%
“…English possesses so many diverse varieties that have led scholars to categorize world Englishes into Inner, Outer, and Expanding Circles. Although there is a shift in the use and users of English, the dominance of native ideology is still prevalent and native accents are more favored than other English accents in both the Outer and Expanding Circles (Carrie, 2017;Chan, 2016;Fang, 2016;Huang & Hashim, 2021;Kuar, 2014;McKenzie, 2015;Phan, 2020;Pilus, 2013;Scales et al, 2006;Weisi et al, 2019). Previous research has shown negative attitudes toward non-native speakers who have a poor accent (Senefonte, 2016).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations